THE CHILD'S TEXT AND THE MIXTURE OF VOICES IN HIS WRITING: AESTHETIC, DIALOGISM AND POLYPHONY ISSUES - Giovani, Fabiana [UNESP]; Camargos, Moacir Lopes de; Souza, Nathan Bastos de (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2016)
Considering the Bakhtinian contributions, one of the objectives of the Human Sciences is to study the text (the statement) and its contexts in relation to the human being. According to Bakhtin, to conceive language as interaction between subjects is to affirm it as constitutively dialogic. The concept of dialogism covers the not always harmonious dialogue between subjects and discourses. Linked to this, Bakhtin defines discursive genres as relatively stable types of utterances, with three characteristics: thematic content, style and compositional construction. It is from the discussion of the dostoevskian novel that Bakhtin introduces the concept of polyphony to the field of language. Expanding this discussion, we will rely on authors who claim that the whole text presents voices to which he responds. This polyphonic conception of the text allows one to examine the presence of the other (as opposed to the enunciator) speech/interlocutor within the text. There is also the double orientation of the subject, who moves between an ethical world and an aesthetic world. The first is the world of life, of the event; The second is the world of finishing and detachment. With such premises, we will analyze, using Ginzburg's index paradigm, texts produced by students who are learning to write from a contextualized language practice, focused on the written production of a discursive genre. Our focus will be the aesthetic finish given to the text and the presence of alterity in the statements, through the presence of other voices, texts/speeches.
Keywords: Aesthetics; Dialogism; Polyphony